Correlation of Month of Birth and Socioeconomic Status with Autism Spectrum Disorder: a Nationwide Study - Ching-Lin Chu; Mei Hung Chi; Chia-Hung Tang; Yi Ting Hsieh; Tzu I Lee; Yen Kuang Yang; Po See Chen (International Journal of Child Development and Mental Health, 2018)
The aim of this study was to investigate whether autism spectrum disorder (ASD) is associated with birth in certain months in Taiwan, as has been found in other countries. A case–control study (1:4) matched according to sex and age was conducted. The study population comprised 4.3% of the population of Taiwan, using the National Health Insurance Research Database (NHIRD) from 1996 through 2008. Multiple logistic regressions were performed after adjusting for socioeconomic factors of urbanization level and income level. A total of 965 people with ASD and 3,860 controls were recruited. In comparison with a March birth, a higher risk of ASD was found for June and August births. After adjusting for level of urbanization and income, the risk of developing ASD was still higher for June, July, and August births over the year. There was higher risk of ASD in urban area when comparing with rural area. A higher risk of ASD was found in the highest income level. A higher risk of ASD was identified among children born in summer months, and a higher risk of ASD in urban area and high socioeconomic status suggested the presence of social-environmental causes of ASD.